Spoligotype-specific risk of finding lesions in tissues from cattle infected by Mycobacterium bovis - Gomez-Buendia, Alberto (BMC Vet Res, 2021)
BACKGROUND: Although the pathogenic effect of members of the Mycobacterium tuberculosis complex in susceptible hosts is well known, differences in clinical signs and pathological findings observed in infected animals have been reported, likely due to a combination of host and pathogen-related factors. Here, we investigated whether Mycobacterium bovis strains belonging to different spoligotypes were associated with a higher risk of occurrence of visible/more severe lesions in target organs (lungs and/or lymph nodes) from infected animals. A large collection of 8889 samples belonging to cattle were classified depending on the presence/absence of tuberculosis-like lesions and its degree of severity. All samples were subjected to culture irrespective of the presence of lesions, and isolates retrieved were identified and subjected to spoligotyping. The association between the presence/severity of the lesions and the isolation of strains from a given spoligotype was assessed using non-parametric tests and Bayesian mixed multivariable logistic regression models that accounted for origin (region and herd) effects. RESULTS: Results suggested a difference in severity in lesioned samples depending on the strain’s spoligotype. An association between specific spoligotypes and presence of lesions was observed, with a higher risk of finding lesions in animals infected with strains with spoligotypes SB0120, SB0295 and SB1142 compared with SB0121, and in those coming from certain regions in Spain. CONCLUSIONS: Our results suggest that strains belonging to certain spoligotypes may be associated with a higher probability in the occurrence of gross/macroscopic lesions in infected cattle, although these observational findings should be confirmed in further studies that allow accounting for the effect of other possible confounders not considered here, and ultimately through experimental studies. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s12917-021-02848-3.